PENGARUH PENILAIAN KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN PADA PT BANK RAKYAT INDONESIA CABANG JAKARTA JOGLO - Aziz Saputra; Shela Indah Savitri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of the study was to determine the effect of work assessment and Work life balance partially and simultaneously on employee performance at PT Bank Rakyat Indonesia, Jakarta Joglo Branch. Using quantitative methods, with a population of 58 employees and a sampling technique using total sampling or saturated sampling, namely the entire population is used as a sample. From the results of statistical calculations, the Work Assessment variable (X1) has a significant effect on the Employee Performance variable (Y). This can be proven by the t-test value of the Work Assessment variable (X1) with a t count of 11.368 and a significance of 0.000. Because t count is smaller than t table (11.368> 2.003) and the significance is smaller than 5% (0.050) then Ha is accepted and H0 is rejected, it can be stated that Work Assessment (X1) has a significant effect on Employee Performance (Y). There is an influence of Work life balance (X2) having a significant effect on the Employee Performance variable (Y). This can be proven by the t-test value of the Work life balance variable (X2) with a t count of 5.063 and a significance of 0.000. Because tcount is greater than ttable (5.063 > 2.003) and the significance is less than 5% (0.050) then Ha is accepted and H0 is rejected, it can be stated that Work life balance (X2) has a significant effect on Employee Performance (Y). It is obtained that there is a significant influence between Work assessment and Work life balance on Employee Performance. Judging from the ANOVA values, the Fcount value is 329.841 while Ftable ( 0.05) for n = 55 is 2.77. So Fcount> from Ftable (0.05) or 329.841> 2.77, with a significant level of 0.000 because 0.000 <0.05, then it can be said that, Work assessment (X1), Work life balance (X2) and together have an effect on Employee Performance (Y).